Strategi Modeling The Way untuk Meningkatkan Keterampilan Berbicara dan Hasil Belajar Peserta Didik di SD Negeri 3 Candisari Purwodadi Kabupaten Grobogan - Hermin Dwi Kurniati; Ervina Eka Subekti; Kuswandari Kuswandari (Universitas Pendidikan Mandalika, 2021)
This study aims to apply the Modeling The Way strategy to improve speaking skills and learning outcomes in learning Theme 9 for fifth grade students of SD Negeri 3 Candisari. This research is a classroom action research conducted in three cycles. The subjects of this study were the fifth grade teachers and the fifth grade students, totaling 14 people. Collecting data through interviews, observation, and documentation. As for the validity of the data using source triangulation and techniques triangulation. The results showed an increase in speaking skills, namely: 1) In the first cycle the first meeting reached 35.71%, 2) the second meeting increased to 42.85%, 3) in the second cycle the first meeting increased to 50%, 4) the second meeting increased to 57.14%, 5) in the third cycle the first meeting increased to 71.42%, 6) the second meeting increased to 85.71%. For learning outcomes also increased, namely: 1) In the first cycle the first meeting reached 35.71%, 2) the second meeting increased to 42.85%, 3) in the second cycle the first meeting increased to 42.85%, 4) the second meeting increased to 42.85% the second meeting increased to 50%, 5) in the third cycle the first meeting increased to 78.57%, 6) the second meeting remained 78.57%. The conclusion of this study is that the Modeling The Way strategy can improve speaking skills and learning outcomes in fifth grade students. SD Negeri 3 Candisari in 2010/2021 academic year.